2009
DOI: 10.1007/s10811-009-9454-5
|View full text |Cite
|
Sign up to set email alerts
|

Monthly variation in the chemical composition of Eisenia arborea J.E. Areschoug

Abstract: The brown alga Eisenia arborea is the second most abundant brown alga along the western coast of the Baja California Peninsula of Mexico. Samples of E. arborea were collected in Bahía Asunción, BCS, over 10 months. Chemical composition was analyzed from dried alga (%, dw): moisture (10.34%), protein (9.44%), ash (24.77%), lipids (0.60%), fiber (5.22%), and carbohydrates (49%). Gross energy was 9.8 kJ g −1 . Seven minerals were analyzed and the four most abundant were K, Na, Mg, and Ca, ranging from 907 to 7,94… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 37 publications
7
31
2
3
Order By: Relevance
“…So, the percentages of FA of G. turuturu in our study showed a difference with those of Hotimchenko (2002) and Denis et al (2010). Furthermore, EPA in G. turuturu was higher compared to that in the brown algae E. arborea (4.9 mg 100 g −1 dw) (Hernández-Carmona et al 2009). An undetermined C16:3 acid was also found in our samples, and the 3-hydroxyheptadecanoic acid was identified in G. turuturu for the second time (Denis et al 2010) up to 3.6 %.…”
Section: Fatty Acid Composition Of Total Lipidscontrasting
confidence: 76%
See 1 more Smart Citation
“…So, the percentages of FA of G. turuturu in our study showed a difference with those of Hotimchenko (2002) and Denis et al (2010). Furthermore, EPA in G. turuturu was higher compared to that in the brown algae E. arborea (4.9 mg 100 g −1 dw) (Hernández-Carmona et al 2009). An undetermined C16:3 acid was also found in our samples, and the 3-hydroxyheptadecanoic acid was identified in G. turuturu for the second time (Denis et al 2010) up to 3.6 %.…”
Section: Fatty Acid Composition Of Total Lipidscontrasting
confidence: 76%
“…Moreover, 3.6 % is higher than that reported for tropical species of Grateloupia: G. indica 1.47 % dw and G. wattii 1.43 % dw (Kumari et al 2010), and it is also higher than in other red seaweeds: Porphyra umbilicalis (3.4 % dw), Chondrus crispus (0.6 % dw), Palmaria palmata (1.6 % dw), and Gracilaria verrucosa (1.3 and 1.5 % dw) (Fleurence et al 1994). Furthermore, it is also higher than in the brown alga Eisenia arborea (0.60 % dw), which is the second most abundant brown alga along the western coast of the Baja California Peninsula of Mexico and is a good candidate to be tested as supplement food for animals, including humans (Hernández-Carmona et al 2009). …”
Section: Lipid Contents and Lipid Class Distributionmentioning
confidence: 99%
“…The fact that this is the first time that a kelp-specific extraction method is used rendering high efficiency explains why the protein content from both temperate and Arctic S. latissima (Fig. 1) was higher than those reported for most other brown algae except Undaria pinnatifida (Fleurence 1999; Hernández-Carmona et al 2009; Westermeier et al 2012), and similar to values obtained in the red alga Hypnea spinella (Suárez-Álvarez et al 2012). …”
Section: Discussionsupporting
confidence: 65%
“…These differences in microelement concentrations of C. Paliurus leaves are likely to be associated with genetic, cultural, harvesting, soil and climatic factors that occur during the growing period in each specific research. Compared to the results from alga and other plants, the concentrations of microelements in the leaves of C. Paliurus were notably lower than these in brown alga (Eisenia arborea) reported by Hernández-Carmona et al (2009), but greater than these in medical herbs (Lovkova et al 2001;Kalny et al 2007), papaya (Hardisson et al 2001) and rice grains (Jiang et al 2008;Wang et al 2009), and dill (Anethum graveolens), (Słupski et al 2005). It is believed that the therapeutic effects of C. Paliurus are related to the physiologically active substances (PAS, such as phenolic compounds, polysaccharide, etc.…”
Section: Discussioncontrasting
confidence: 85%